2019
DOI: 10.1111/jcpt.12852
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a flow chart–like risk prediction model of ganciclovir‐induced neutropaenia including severity grade: A data mining approach using decision tree

Abstract: What is known and objective Haematological toxicities such as neutropaenia are a common side effect of ganciclovir (GCV); however, risk factors for GCV‐induced neutropaenia have not been well established. Decision tree (DT) analysis is a typical technique of data mining consisting of a flow chart–like framework that shows various outcomes from a series of decisions. By following the flow chart, users can estimate combinations of risk factors that may increase the probability of certain events. In our previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…2) Previous studies have constructed risk prediction models of adverse drug reactions (ADRs) using DT analysis. 3,4) These findings strongly indicate that ML can replace or compensate for older techniques.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…2) Previous studies have constructed risk prediction models of adverse drug reactions (ADRs) using DT analysis. 3,4) These findings strongly indicate that ML can replace or compensate for older techniques.…”
Section: Introductionmentioning
confidence: 79%
“…DT models have a flowchart-like framework, so users can easily evaluate the risk of ADRs compared to conventional statistics models. 3,4) In addition, DT models are suitable for clinical application because users do not require any special software, unlike other ML methods. 3,4) Therefore, in this study, we selected a DT model to validate the usefulness of ML for drug dose setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 15 (44%) of 34 studies assessed the performance of a single AI model. 13,14,16,17,20,26,[30][31][32]34,36,37,41,42,44 The other studies compared the performance of multiple models with neural networks and tree-based algorithms demonstrating the best performance based on accuracy and AUC-ROC, or other metrics reported in the studies. One study showed similar performance between federated learning (ie, training algorithms using multiple decentralised databases) and centralised approaches for development of AI-based ADE prediction models.…”
Section: Prediction Use Casesmentioning
confidence: 99%
“…Furthermore, the adverse reactions in the two groups were compared, showing that the children suffered from adverse reactions including gastrointestinal reactions, leucopenia, thrombocytopenia, dizziness, and pruritus, which have been mentioned in previous studies (24), and there was no significant difference in adverse reactions between the two groups. Although the total adverse reaction rate of the Obs group was lower than that of the Con group, the difference was insignificant.…”
Section: Discussionmentioning
confidence: 77%